FORMS OF CONCENTRATION OF ORE ELEMENTS IN CARBON-RICH METASOMATITES - Danilova Yu.V.; Danilov B.S.; Shumilova T.G. (My University, 2006)
The problem of endogenic carbonification of rocks and related ore mineralization is topical for many reasons. The possibility of accumulation and transfer of various metals with reduced carbon-rich fluids has been proved. However, several questions concerning the mode of transfer and forms of deposition of elements in carbonized rocks remain open. In the deep fault zones of the southern framework of the Siberian Craton, the degree of structural perfection of native forms of carbon and forms of metal concentration in graphite closely interrelate and depend on PT conditions of tectonite formation.